2021
DOI: 10.1126/sciadv.abe2943
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered electro-tactile system for virtual tactile experiences

Abstract: Tactile sensation plays important roles in virtual reality and augmented reality systems. Here, a self-powered, painless, and highly sensitive electro-tactile (ET) system for achieving virtual tactile experiences is proposed on the basis of triboelectric nanogenerator (TENG) and ET interface formed of ball-shaped electrode array. Electrostatic discharge triggered by TENG can induce notable ET stimulation, while controlled distance between the ET electrodes and human skin can regulate the induced discharge curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
147
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 193 publications
(148 citation statements)
references
References 42 publications
0
147
0
1
Order By: Relevance
“…(f) Self-powered electro-tactile system for spacesuit (Reprinted with permission from ref. [317]. Copyright 2021 Science).…”
Section: Aircraft and Aerospacementioning
confidence: 99%
See 1 more Smart Citation
“…(f) Self-powered electro-tactile system for spacesuit (Reprinted with permission from ref. [317]. Copyright 2021 Science).…”
Section: Aircraft and Aerospacementioning
confidence: 99%
“…In aerospace, as shown in Figure 10f, Shi et al reported a self-powered electro-tactile (ET) system for the massive space suit [317]. The ET system is based on electrostatic discharging triggered by a series of contact-separation TENGs below the spacesuit.…”
Section: Aircraft and Aerospacementioning
confidence: 99%
“…(k) Electrical discharge based feedback system using TENG array with ball electrode. Reprinted with permission from Reference [309], Copyright 2020, AAAS. (l) A multi-modal sensing and feedback glove with liquid metal based resistive strain sensor, vibrator, and thermal feedback units.…”
Section: Haptic-feedback Enabled Hmismentioning
confidence: 99%
“…Moving forward, TENG is also directly used as a feedback unit via the generated voltage. As shown in Figure 7k, Shi et al designed a TENG array with ball electrodes to make a feedback system for VR [309]. When the slider is sliding across the TENG array, the electrical output can be generated via the triboelectrification effect.…”
Section: Haptic-feedback Enabled Hmismentioning
confidence: 99%
“…In order to meet practical applications, single-function tactile sensors are developing towards multifunction use in terms of being self-powered, visualization capabilities, biodegradability, being self-healing, etc. [ 27 , 28 , 29 , 30 , 31 , 32 ]. Among them, we focus on the recent representative development of high-resolution, high-sensitivity, self-powered, and visualization capabilities which are also the key development direction of flexible tactile sensing in the future.…”
Section: Introductionmentioning
confidence: 99%